Strategi Relokasi Inovatif: Solusi Pemerintah Kota Untuk Pedagang Kaki Lima Pasar Sentral Makassar Pasca Kebakaran - Rahman, Abd.; Jusman, Jusman; Mappiwali, Hermawati (LPPM Institut Pendidikan Nusantara Global, 2024)
The Makassar City Central Market resulted in large losses for street street vendorsa fire occursforcing city governments to formulate effective relocation strategies. This research aims to evaluate innovative relocation strategies implemented as a solution to restore the economic conditions of street vendors after the fire. Through a participatory approach, the city government involves traders in the planning and implementation of relocation, ensuring that their needs and aspirations are met. Meringue with approach consultation and public participation, by providing brother strategic areas, adequate facilities, and den empowerment approach training and business assistance to help traders adapt to the new environment. Building partnerships by strengthening available support, while regular monitoring and evaluation ensures program sustainability. The research results show that this strategy has succeeded in restoring and redeveloping the street vendor economic sector, creating a more stable and sustainable market environment. These findings emphasize the importance of a comprehensive and collaborative approach in dealing with crises, and provide practical guidance for local governments in dealing with similar situations in the future.